Peran Teknologi Dalam Meningkatkan Efektivitas Proses Pembelajaran IPS - Bagus Setiawan; Eprinda Nurro’in Habibah; Adela Putri Rahmadani; Dennisa Fatma Novita Ardianti (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
The research conducted aims to empirically measure the impact of the use of technology in the teaching and learning process. It involves monitoring, measuring, and analyzing the effectiveness of technology in improving student understanding, information retention, and learning outcomes.  evaluate education policies that support or hinder the integration of technology in teaching and learning.  In this modern era, technology has become an integral component in education, with significant implications on how learning and teaching are conducted.  The method used is a descriptive method with a Library Reaserch approach.  One of the paradigm changes in education is inclusive education.  The early history of special education in Indonesia is known for the implementation of 3 types of schools, namely Special Schools (SLB), Extraordinary Elementary Schools (SDLB), and Integrated Schools. The use of technology in the Social Sciences (IPS) learning process has the potential to enhance the learning experience, however, it also involves a number of challenges and obstacles that need to be overcome. Although technology can be a powerful tool in social studies learning, some concepts or learning methods may not be effectively realized through technology. This requires creative thinking and adaptation to stay fit for learning objectives.